THE EFFECT OF E-LEARNING ON SENIOR HIGH SCHOOL STUDENTS' LEARNING OUTCOMES IN ENGLISH SUBJECT DURING THE NEW NORMAL ERA - Balqis Husain; Linia Tira Lediya Reka (Universitas Muhammadiyah Lampung, 2023)
Aims of this research was to determine the effect of E-learning on the learning outcomes of high school students in English subject in the new normal era conducted at SMA N 1 Pulau Morotai. This research uses a qualitative research design with descriptive qualitative data analysis methods and uses a perpose sampling technique. ThisÂ research uses a questionnaire as a research instrument. There are 50 statements about the problems faced by students during E-learning and 25 statements about the impact felt by students during E-learning. The number of students who were sampled in this research found 103 respondents from class XI Mipa and IIS. The researcher used SPSS to calculate the data. The results obtained the value of Sig (a) is 0.00. This means that the value of Hi is accepted because Sig <a = 0.05. In other words, it can be said that there is a significant effect when using E-learning as a learning method in the new normal era at SMA N 1 Pulau Morotai.